Non-resident travellers entering Canada, by country of residence (excluding the United States) - Statistics Canada (Government of Canada, 2018)
This table contains 3549 series, with data for years 1972 - 2018 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...) Country of residence (273 items: Total non-resident travellers, countries other than the United States; North America, Central America and Caribbean, total; Anguilla; Antigua and Barbuda; ...).